Transfer of philosophy into the medicine on an example of ‘human enhancement’ debate - Zagorac, Ivana (Array, 2010)
“Therapy vs. enhancement” is well-known debate in bioethical field. This controversial topic is interrelated with many other bioethical issues, mainly those referring to medicine. Questions of ‘nature’, ‘human’, ‘will’, ‘progress’, ‘dignity’, ‘freedom of choice’, and ‘informed consent’ are often discussed in this context. Argumentation usually draws attention to the classics of philosophical and ethical thought, with often misinterpretations. In a framework of the “human enhancement” debate paper focuses on some of the philosophical and ethical arguments, mainly those referring to ‘nature’. They are used as an example of misreading and misinterpretation of core ethical and philosophical terms which are consequently transferred into legal documents.